Distributed Computing Services on top of a Research and Education Network: GARR - Mantovani, Maria Laura; Ruggieri, Federico (My University, 2013)
Since the beginning of 2013 the Italian National Research and Education Network GARR has started a new Distributed Computing and Storage Department (DCSD). The new DCSD in the Italian NREN, follows the new mission of GARR that will not only provide very advanced Network services to the Research community, but also manage, consolidate and expand an Italian Distributed Computing and Storage Infrastructure based on Grid and Cloud. This paper provides state of the art information on the planning and deployment of such infrastructure presenting the motivations, the objectives and the vision that will bring this infrastructure into the next Horizon 2020 programme of the European Commission. The first pillar of this strategic evolution of GARR is the new project "GARR-X Progress" which has been recently approved by the Italian Ministry of Research and Education and that aims to deploy an advanced e-Infrastructure in the south of Italy (Regions of Convergence). GARR-X Progress will use a new fibre optics backbone and deploy a new distributed system of 6.000 Virtual CPUs and more than 6 PB of storage.
Keywords: Cloud; NREN; Distributed Computing; Distributed Storage; Advanced Services